Workplace bullying and work engagement amongst teachers: a job demands-resources perspective - Ross, Tamsyn (My University, 2023)
Within the many South African schools across the country, the prevalence of workplace bullying, from both colleagues and supervisors alike, has increased substantially. In addition to the failing educational system, which brings about many different challenges, teachers are subjected to working in highly toxic environments, whereby substantial demands coexist with limited resources. Using the Job-Demands Resources model as a framework, we are able to better understand how in these environments, workplace bullying flourishes. As severe organisational and individual consequences arise as a result of workplace bullying, such as being disengaged from work itself, it is imperative to reduce the number of incidents occurring. This research aimed to determine the prevalence of workplace bullying amongst teachers in Gauteng and its relationship to work engagement. Furthermore, the extent to which the relationship between workplace bullying and work engagement is moderated by job demands and job resources was also explored. Within the current study, which utilised secondary data, participants were required to complete a survey comprising four questionnaires, namely a Demographic Questionnaire, the Job Demands-Resources Scale, the Negative Social Acts Questionnaire-Revised (which measures workplace bullying) as well as the Utrecht Work Engagement Scale. Teachers (n=158) from 14 schools across Gauteng comprised the final sample. Results indicated that workplace bullying was significantly correlated to work engagement, in addition to its subcomponents of vigour, dedication and absorption. Further, a significant relationship between workplace bullying and both job demands and job resources, known collectively as job characteristics, was established. These findings aligned with previous literature. Moderated Multiple Regression revealed the moderating effect of job resources on the relationship between workplace bullying and work engagement, and its subcomponents. However, these results were unexpected, as reverse-buffering effect was reported. In the presence of higher job resources, the impact of workplace bullying on work engagement worsened. Despite job demands being significantly associated to workplace bullying, job demands was not found to moderate the relationship between workplace bullying and work engagement or its subcomponents. These counterintuitive findings are discussed along with the limitations of the present study as well as future recommendations.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts by Coursework and Research Report in the field of Organisational Psychology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2023